2018
DOI: 10.1111/imb.12535
|View full text |Cite
|
Sign up to set email alerts
|

Identification and expression analysis of the Spodoptera exigua neuropeptidome under different physiological conditions

Abstract: Neuropeptides are small signalling molecules acting as neurohormones, neurotransmitters and neuromodulators. Being part of the chemical communication system between cells within an organism, they are involved in the regulation of different aspects of animal physiology and behaviour such as feeding, reproduction, development and locomotion. Transcriptomic data from larval and adult tissues have been obtained and mined to generate a comprehensive neuropeptidome for the polyphagous insect pest Spodoptera exigua. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(30 citation statements)
references
References 61 publications
1
29
0
Order By: Relevance
“…Adipokinetic hormone (AKH) is a neuropeptide involved in energy mobilization (Alves‐Bezerra et al, 2015; Gade, 1990) and in stress response (Velki, Kodrík, Večeřa, Hackenberger, & Socha, 2011). Unlike most insect orders that have one, Lepidoptera genomes encode two AKH paralogues (Kanost et al, 2016; Roller et al, 2008; Zhan et al, 2011); this has been confirmed by transcriptomic analysis in several species (Diesner et al, 2018; Llopis‐Giménez, Han, Kim, Ros, & Herrero, 2019; Xu et al, 2016). This observation is confirmed by our results; two AKH transcripts were detected in P. interpunctella transcriptome, probably reflecting the existence of two paralogue PloinAKH genes (Table 1, Supplementary Information 1 and 2).…”
Section: Resultsmentioning
confidence: 91%
“…Adipokinetic hormone (AKH) is a neuropeptide involved in energy mobilization (Alves‐Bezerra et al, 2015; Gade, 1990) and in stress response (Velki, Kodrík, Večeřa, Hackenberger, & Socha, 2011). Unlike most insect orders that have one, Lepidoptera genomes encode two AKH paralogues (Kanost et al, 2016; Roller et al, 2008; Zhan et al, 2011); this has been confirmed by transcriptomic analysis in several species (Diesner et al, 2018; Llopis‐Giménez, Han, Kim, Ros, & Herrero, 2019; Xu et al, 2016). This observation is confirmed by our results; two AKH transcripts were detected in P. interpunctella transcriptome, probably reflecting the existence of two paralogue PloinAKH genes (Table 1, Supplementary Information 1 and 2).…”
Section: Resultsmentioning
confidence: 91%
“…Experiments showed that CCHamide is connected to feeding, sensory perception and the control of insulin like peptides in Drosophila melanogaster (16)(17)(18) and connected to feeding in other insects (5,19). Its expression in different larval or adult insects is connected to the digestive system (7,(18)(19)(20)(21)(22). Experiments with EP showed a myo-excitatory effect that included digestive tissues of oligochaetes (6), leeches (23,24), and a gastropod species (25), and association with digestive tissues was also shown by immunohistochemistry on a polychaete (26).…”
Section: Introductionmentioning
confidence: 92%
“…The behavioral effect of a single type of peptide on different animals has only been tested for FMRFamide and its orthologue FLRFamide and the different studies showed some species-specific effects in different trochozoan larvae (41,(43)(44)(45). The influence of EP on locomotion of L. longissimus larvae and the broad expression in the brain and prominent ventral nerve cord of the juveniles stands in contrast to the myo-excitatory effect of EPs in different adult/juvenile annelid (6,23,24,26) and mollusc (25) species and the repeated association of EPs and CCHamides with feeding or the digestive system in annelids (6,23,24,26,64), molluscs (25,65) and insects (5,7,(16)(17)(18)(19)(20)(21)(22)) (see also table 2). This suggests that the degree of functional conservation can vary depending on the type of peptide, the animal taxon or the developmental stages and that also functionally more conserved peptides like the EP/CCHamides can show plasticity in their behavioral association.…”
Section: Functional Association Of Peptides Can Vary During Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, more neuropeptides have been identified using neuropeptidome in Lepidoptera (Llopis-Gimenez, Han, Kim, Ros, & Herrero, 2019;Roller et al, 2008;Xu et al, 2016). Two transcripts encoding CCHamides were found in the head transcriptome (Figure 4a).…”
Section: Cchamidementioning
confidence: 99%